The Significance of Phallocentrism as Illustrated on Grace Paley’s Wants - Pasopati, Rommel Utungga; Pujimahanani, Cahyaningsih; Putri, Adinda (Institut Agama Islam Negeri Ponorogo, 2024)
This article would like to expose matter of phallocentrism in short story written by Grace Paley entitled Wants. Phallocentrism itself plays role as the dictations of values of male against female beings. Grace Paley’s short story published in 1974 and tells a woman’s perspective that is so slow and simple in wanting anything. Her ex-husband has certain dream to be achieved, but she only wants to be a good mother and be happy. Through qualitative method on cultural studies, this paper depicts dictation of a man to his ex-wife. This is in line with dictation of man in phallocentrism theorized by Ernest Jones. The woman actually has done many intangible things, but those meant nothing for the man as he wants tangible ones. The man wants to run but the woman prefers to walk. Both of them are lost in time of being together since the ex-husband’s side is too dominant for the ex-wife’s part. In conclusion, the short story explains total difference due to radical dominance instead of living dialogues between man and woman.